Sistema de aquisição de dados sincronizado integrado com webcam para processos de soldagem baseado em LabView - Silveira, Fernanda Mendonça (2006)
The development of data acquisition techniques able to monitor the performance of an automated welding system could be, for example, applied to a system able to repair pipes full of operating fluid. In this case, the system must precisely control and monitor the heat input during the weld. For this purpose, it would be necessary to develop data acquisition techniques able to monitor the performance of such a system. Digital oscilloscopes, which are usually the kind of equipment used for this purpose, present high-cost as well as other solutions offered by the market. Moreover, those systems do not offer a specific solution to the welding area. Thus, the aim of this work was to develop a synchronized data acquisition system with integrated webcam that was suitable for the study of the several types of welding processes. It could be used for automation of pipeline repair systems, as well as, for other types of welding operations, including experimental evaluations into laboratories. A software package was developed using LabVIEW as programming language. It is able to do synchronized acquisition of signals and image and post analysis of the acquired data. The use of low-cost cameras like webcams was introduced aiming to determine arc characteristics as arc length, for instance. The acquisition of the emitted sound by the arc during the welding was also considered, what could increase the feeling of the professional working away and could be used for studies related to welding quality. Using the existent resources in the laboratory, a hardware prototype with enough flexibility and suitable for several types of welding processes was designed. Afterwards, a system with a physical configuration more appropriate to the work environment and lower cost was built. This system was assessed with two different welding operations, Gas Metal Arc Welding and Resistance Spot Welding, when its limitations and advantages were explored and identified.